Transforming medical healthcare through research - Abdul Rahim, Roslina; Othman, Ahmad Faidzal; Kamarulzaman, Mohd Nazli (IIUM Press, 2023)
The research book contains an introduction, fifteen research chapters that being divided into three parts and overall conclusion as the final chapter of this book.There are three major parts of this book which are the Basic medical science research, clinical research and case series. All chapters are peer-reviewed and carefully selected by the expertise of each area. The research work that is highlighted in this book spans the spectrum of medical sciences, from fundamental to clinical, to case series and all these research work being carried out during the pandemic. All the images describe in this book are obtained with consent from the patients and it help explaining the research works. This book is written and edited in a such way that is simple and easy for the readers to understand on how the research work being conducted and all the scientific findings were clearly explained. It is hopeful that the work would contribute and support the transformation of healthcare, especially in this post-pandemic era. In the spirit of knowledge sharing, open access and sustainable and responsible research, we hope that the addition information to the body of knowledge could further enhance and encourage further research likewise.